Prinsip Futuristik Pada Perancangan Fitness And Leisure Centre - Nurul Syahirah; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru as the capital city of Riau Province which is growing rapidly has a community that has a high appreciation of the development of the world of sports today, for example is bodybuilding sports. But the people of Pekanbaru City do not yet have adequate fitness and leisure center facilities and need them to fulfill their sports activities in addition to using their free time to be more positive and beneficial. The application of Futuristic Themes used in the design of the Fitness and Leisure Center is in the background by building functions that are in accordance with the character of the development of knowledge about healthy lifestyles and the technology of the tools used to support the building's function where this is in accordance with Futuristic principles that are in line with development technology with increasingly advanced technology, futuristic existence will also grow.Keyword: Bodybuilding, Fitness and Leisure Centre, Futuristic, Technology